Heart rate responses to uphill walking in 9- to 10-yr-old boys and girls - Jereb, Blaž (Kinesiologia Slovenica, 2003)
The objective of our study was to analyse the exercise intensity during uphill walking and to find out if there were any differences in heart rate (HR) between boys and girls. For the purpose of the study, a group of seven boys and twelve girls who were not equally physically fit made three mountain walking trips at different pace (directed pace, paces on the aerobic thresholds of the boys in the best and poorest physical condition). The walking trips took place over three weeks, olways on the same day of the week, startind at the same hour. HR of the children was measured with Polar Coach measuring devices every fifteen seconds. Before and after the exercise, no differences in HR were found between boys and girls. The results expressed in percentages of individual aerobic threshold show that walking was too hard for some of the children in the group. If the activity continued, it could be damaging or even dangerous for their cardiovascular system. On those children in the group who walked under their aerobic threshold walking didn't have any physiological impact. Consequently, we would recommend that groups of children taken to mountains should be homogeneous.
Keywords: aerobni prag; frekvenca srca; hoja; otroci; planinstvo